Confronting the figure of the “mad scientist” in psychedelic history: LSD’s use as a correctional tool in the postwar period - Jones, Andrew (Frontiers in Psychology, 2023)
Since reports about CIA-funded LSD studies came out in the 1970s, psychedelic drugs have invoked images of unethical experimentation and “mad scientists” in the public imagination. Even now, as the stigma surrounding psychedelics diminishes in the 21st century, the figure of the “mad scientist” continues to occupy a space in what Ido Hartogoshn calls the “collective set and setting,” the larger framework of cultural understandings that shape how individuals experience psychedelic drugs. Scientists and humanities scholars who study these drugs have responded to this issue by drawing boundaries between those who used psychedelics carefully and those who used them ignorantly. Yet these boundaries were not always so clear in the past. Drawing on historical examples of LSD’s use as a correctional tool in Canada, I show how enthusiasm about the drug’s potential led several experienced and knowledgeable psychedelic therapists to use it on vulnerable populations in diverse institutional settings, such as correctional facilities. These examples reveal how the institutional context of modern industrial societies shaped the application of psychedelic therapy in the past and suggest that today’s therapists need to carefully consider how this broader context impacts their work.